POLA PEMBINAAN ATLET PANJAT DINDING GAJAH MADA CLIMBING CLUB MEDAN - Rudy Harto S., Teddy (Indonesia Sport Journal, 2024)
This study aims to determine the Coaching Pattern of Gajah Mada Climbing Club Medan Athletes in 2018. The research method is descriptive qualitative with interview, observation, documentation, and triangulation techniques. The research subjects were 26 people while the informants in the study were 1 administrator, 1 coach, and 3 athletes. The results of this study indicate: (1) The planning carried out made the athletes' achievements taken into account at the provincial and national levels (2) The organizational system collaborates with FPTI North Sumatra, the budget comes from athletes' and administrators' self-help, the organizational structure only consists of a chairman, secretary, treasurer and manager. (3) The movement of the coach gives instructions in a firm, disciplined manner, and is respected by his athletes but outside of being a kind-hearted religious figure, often communicating with athletes and being considered as parents for his athletes. (4) The supervision system with evaluation every time the training runs after the training will end with motivations, as well as before and after participating in the match so that it can be improved in the future.